2017
DOI: 10.1007/s10853-017-0838-7
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of lithium-substituted bioactive glasses to tailor cell response for hard tissue repair

Abstract: Bioactive glasses (BG) are used clinically because they can both bond to hard tissue and release therapeutic ions that can stimulate nearby cells. Lithium has been shown to regulate the Wnt/β-catenin cell signalling pathway, which plays important roles in the formation and repair of bone and teeth. Lithium-releasing BG, therefore, have the potential to locally regulate hard tissue formation; however, their design must be tailored to induce an appropriate biological response. Here, we optimised the release of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 39 publications
2
34
0
Order By: Relevance
“…However, the angiogenic effects of Li + released from biomaterials have not yet been assessed. The studies that have examined the effect of the addition of Li + into different biomaterials have focused on the evaluation of the physicochemical and structural properties as well as on the osteogenic potential of some of them [ 18 , 19 , 22 , 23 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. In particular, the incorporation of Li + into bioactive glasses was first described by Khorami et al, who partially substituted Na 2 O by variable amounts of Li 2 O (3, 7, and 12 wt %) in a bioactive glass in the SiO 2 -CaO-Na 2 O-P 2 O 5 (45S5) system [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the angiogenic effects of Li + released from biomaterials have not yet been assessed. The studies that have examined the effect of the addition of Li + into different biomaterials have focused on the evaluation of the physicochemical and structural properties as well as on the osteogenic potential of some of them [ 18 , 19 , 22 , 23 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. In particular, the incorporation of Li + into bioactive glasses was first described by Khorami et al, who partially substituted Na 2 O by variable amounts of Li 2 O (3, 7, and 12 wt %) in a bioactive glass in the SiO 2 -CaO-Na 2 O-P 2 O 5 (45S5) system [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…These results are in agreement with the recent findings of Bruckner et al using 45S5 microparticles (<38 µm) with 6.1 to 24.4% (mol %) of Li 2 O [ 33 ], as well as with the data reported by Miguez-Pacheco et al for glass-ceramic scaffolds derived from the 45S5 bioactive glass with 2.5, 5, and 10 wt % of Li 2 O, which showed that a content of up to 5 wt % of Li 2 O keeps the bioactive behavior and thermal characteristics of the 45S5 glass [ 34 ]. On the other hand, it has been demonstrated that ion release from lithium-substituted BG can be tailored to induce an appropriate biological response [ 41 ]; for example, the partial replacement of Na 2 O by up to 5 wt % of Li 2 O in the 45S5 bioactive glass [ 34 ] ensures the release of Li + within therapeutic levels for humans (0.5–1.2 mmol) [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several papers deal with the investigation of novel compositions of silicate and phosphate bioactive glasses, in particular glasses with therapeutic ion delivery capability to enhance cellular response, an area highlighted in one of the most recent papers authored by Larry Hench in 2015 [6], which reflects the importance of this topic for applications of bioactive glasses in regenerative medicine and as antibacterial agent. For example, novel bioactive silicate glasses (both melt-derived and solgel produced) incorporating B [7,8], bivalent ions such as Mg, Zn, Sr and Cu [9], Li [10], Ce [11], Sr [12,13], Cu, Zn [14], Mn [15], are discussed. The release of ''classical'' ions in bioactive glasses, namely Si, Ca, P, is the subject of the studies of Houreh et al [16] and Obata et al [17] in the context of dental pulp stem cells and osteoblast cell responses, respectively.…”
Section: ó Springer Science+businessmentioning
confidence: 99%
“…Bioactive glasses degrade when in contact with body fluids, release ions and mineralize a surface layer of biomimetic apatite . In the last years, one main focus in bioactive glass research was the incorporation of therapeutically active ions such as strontium, lithium, or cobalt for controlled release. One key part of early‐stage bioactive glass characterization is immersion in simulated physiological solutions, to investigate in vitro ion release and apatite surface mineralization.…”
Section: Introductionmentioning
confidence: 99%